2021
DOI: 10.21608/ejchem.2021.99957.4868
|View full text |Cite
|
Sign up to set email alerts
|

Association of C-Reactive Protein with Risk of Complications of diabetic nephropathy

Abstract: Background: Diabetic nephropathy become the main cause of chronic renal diseases in the world, that have been demonstrated high mortality rate and disability in patients with diabetes mellitus. Many recent studies demonstrate the associations of CRP and development of renal impairment in type two diabetic patients demonstrating the relation between systemic inflammation and glycemic control and consequently with severity of diabetic complications. Aim of study: evaluate the role of CRP and to analyze any corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In agreement with our study CRP plays an important role in mesenchymal cell proliferation by release of proinflammatory cytokines in addition to increase glomerular albumin permeability which finally lead to albuminuria [16]. This result agrees with [17] who found that there was a significant higher CRP level in patients' group than that of healthy control group and the concentration of CRP in serum samples was higher in diabetic patients with nephropathy than those without nephropathy. [18] reported that microalbuminuria was accompanied by elevated HsCRP, suggesting activation of inflammatory pathways in the progression of renal disease in Type 2 diabetic patients which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our study CRP plays an important role in mesenchymal cell proliferation by release of proinflammatory cytokines in addition to increase glomerular albumin permeability which finally lead to albuminuria [16]. This result agrees with [17] who found that there was a significant higher CRP level in patients' group than that of healthy control group and the concentration of CRP in serum samples was higher in diabetic patients with nephropathy than those without nephropathy. [18] reported that microalbuminuria was accompanied by elevated HsCRP, suggesting activation of inflammatory pathways in the progression of renal disease in Type 2 diabetic patients which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…(p<0.001). 25 The mean urea level in the Group with normal CRP levels was 30 mg/dl with std deviation of 8.5 mg/dl The mean urea level in the group with elevated CRP was 34.2 mg/dl with a std deviation of 13.5 mg/dl. The difference between the two groups was statistically significant (p<0.001).…”
Section: Discussionmentioning
confidence: 84%
“…C-reactive protein is a pentraxin family plasma protein that is produced by hepatocytes. Its expression is controlled by inflammatory cytokines produced by adipocytes, such as interleukin 6 (IL-6), and it serves primarily as an anti-inflammatory and proinflammatory molecule [18,19]. By attaching phospholipids, phosphocholine, chromatin, fibronectin, and histone, it plays a crucial role in the identification and elimination of infections and damaged cells [20,21].…”
Section: Discussionmentioning
confidence: 99%